AGE-RELATED-CHANGES OF GLUTATHIONE CONTENT, GLUTATHIONE-REDUCTASE AND GLUTATHIONE-PEROXIDASE ACTIVITY OF HUMAN ERYTHROCYTES - Matsubara, Luiz Shiguero [UNESP]; Machado, PEA (Associação Brasileira de Divulgação Científica (ABRADIC), 1991)
1. In order to investigate the effect of aging on the erythrocyte glutathione system, total glutathione (GSH), glutathione reductase (GSH-red) and glutathione peroxidase (GSH-px) levels were measured in erythrocytes from 33 young (mean age = 30.5 +/- 9.7 years) and 28 aged (mean age = 68.9 +/- 11.4 years) healthy individuals.2. GSH was 3.5 +/- 1.8-mu-M/g Hb for the young group, a value significantly greater (P < 0.01) than 2.3 +/- 0.9-mu-M/g Hb found for the aged group. Similarly, GSH-red activity, 5.5 +/- 1.8 IU/g Hb, was higher (P < 0.05) for the young group than 3.4 +/- 0.9 IU/g Hb found for the aged group. The GSH-px activity levels for the young group, 21.1 +/- 5.9 IU/g Hb, were significantly greater (P < 0.01) than 12.0 +/- 3.3 IU/g Hb for the aged group. The lower activity detected in the aged group for all of these parameters of the glutathione redox system was not related to low levels of hematocrit or hemoglobin.3. There was no statistical difference in the activation coefficient (AC) of reductase (+FAD/-FAD) between groups, which seems to indicate that the lower activity of glutathione reductase observed in the aged group was not due to riboflavin deficiency.4. Additional information is required to determine the mechanisms controlling the glutathione redox system and its role in the aging process.
Keywords: GLUTATHIONE; GLUTATHIONE REDUCTASE; GLUTATHIONE PEROXIDASE; AGING